A rare case of low voltage electrical injury leading to bilateral femur fractures and vertebral body fractures: A case report and review of the literature. (July 2021) - Ritchie, David; Elkbuli, Adel; McKenney, Mark; Renda, Michael
Abstract: Introduction and importance: Low voltage electrical injuries (less than 1000 V) can produce enough tetany to cause fractures, usually of the upper extremities. Simultaneous bilateral fractures of the femoral neck are an extremely rare occurrence. It is even more uncommon for a young healthy male to suffer significant fractures from a low voltage injury. Case presentation: A 25-year-old male attempted suicide by filling a bathtub with water and getting into it prior to dropping a blender into the water. He experienced full body convulsions but remained awake throughout the entire event. In the trauma bay his primary complaints were bilateral hip pain and back pain, without neurologic deficit. Radiological studies confirmed bilateral sub-capital femur fractures and thoracic vertebral fractures (compression fractures of T3, T4, T5, T6, T7, T9, and T11). The patient underwent bilateral open reduction and internal fixation (ORIF) of the femurs, while the spine fractures were treated with a thoracic-lumbar-sacral orthosis TLSO brace. Clinical discussion: Low voltage electrical injury is more likely to lead to fractures in patients with chronic renal failure and metabolic conditions such as hypocalcemia, osetomalacia, and osteoporosis. Fractures after low voltage electrical injury are extremely uncommon and a high suspicion for these injuries should be maintained because if missed there is a high risk of morbidity and mortality. Conclusion: We present a rare case of low voltage electrical injury by 120 V from a domestic US power supply, amplified by water conduction resulting in bilateral femoral neck fractures and vertebral body fractures. Highlights: Fractures resulting from low voltage electrical injury are usually related to chronic renal failure, and metabolic conditions such as hypocalcemia, osetomalacia, and osteoporosis. Electrical injuries require a thorough assessment including voltage, duration of injury, environment (wet skin or humid environment), and any existing comorbidities. Bilateral femure and vertebral fractures are rare injuries following low-voltage electrical injury.